Entre el llenguatge i la realitat: vint anys de poesia catalana - Calafat, Francesc (Caplletra. Revista Internacional de Filologia, 1997)
Between 1970 and 1990, Catalan poetry experienced a significant increase in new authors and works, that followed in succession the already established authors like Espriu, Foix, Estellés, Vinyoli and Martí ï Pol, amongst others. Here the fundamental characteristics of these new authors and their poetry are analized. A characterization of the most remarkable poets is also studied.